Bilirubin Level Detection Using Different UV Light - Awg Ajis, Dayang Dyanna (Universiti Teknologi PETRONAS, 2017)
Phototherapy is one of the commonly used form of treatment for neonatal jaundice. It operates by exposing an infant to a certain light source. The most conventional ones are fluorescent lamp, halogen bulb, fibre optic and also light emitting diodes (LED). Currently, blue LEDs are favourable as it has long bulb life, low heat production and has a low cost. The determination of the efficiency of blue LEDs are to be calculated by observing the decrement concentration of the food colouring solution which represents bilirubin. In this experiment, blue LEDs are being compared to the commonly used UV fluorescent lamps. A spectrophotometer is used to retrieve data from the solution. The results of the experiment shows that the blue LEDs are 10% more efficient than UV fluorescent lamps in terms of colour difference for a 6 hour experiment.